A ZIF-67 modified NiFe-LDH absorbing material, preparation method and application

By inlaying ZIF-67 multi-faces in NIFE-LDH materials, ZIF-67 modifies the Nife-LDH suction material, solve the problem of insufficient Nife-LDH material's dielectric capacity, and realize the stronger electromagnetic wave absorption ability and better Image matching characteristics.

CN116282221BActive Publication Date: 2025-01-28NORTHWEST UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310210516.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-06
Publication Date
2025-01-28
Estimated Expiration
2043-03-06

AI Technical Summary

Technical Problem

The existing NiFe-LDH materials have weak dielectric capabilities, which limits their application in the field of electromagnetic wave absorption. A material that is urgently needed to modify NiFe-LDH to improve the absorption characteristics.

Method used

By inlaying the ZIF-67 multi-facial body in the flower-shaped Nife-LDH sheet layer, the ZIF-67 modifies the Nife-LDH suction material. It uses a simple preparation method. The process is simple and the cost is suitable for large quantities.

Benefits of technology

The electromagnetic wave absorption capacity of the material has been improved, the loss mechanism is stronger, the impedance matching is better, and the electromagnetic waves can be effectively absorbed within the broadband range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004112565960000011
    Figure HDA0004112565960000011
  • Figure HDA0004112565960000012
    Figure HDA0004112565960000012
  • Figure HDA0004112565960000021
    Figure HDA0004112565960000021
Patent Text Reader

Abstract

The invention discloses a ZIF-67 modified NiFe-LDH absorbing material, a preparation method and an application thereof, including a flower-shaped NiFe-LDH with a lamella, wherein a ZIF-67 polyhedron is inlaid between the flower-shaped NiFe-LDH lamellae; in the flower-shaped NiFe-LDH, the molar ratio of the Ni source compound to the Fe source compound is (9-1):1; the mass ratio of ZIF-67 to NiFe-LDH is 2:(3-5). The composite material has an optimal reflection loss of 77.97dB for electromagnetic waves at a frequency of 5.43GHz; the optimal bandwidth is 6.42GHz (11.58-18GHz), and the matching thickness is only 2.02mm. The absorbing material prepared by the method of the present invention has a wide bandwidth, high reflection loss, simple preparation process, low cost, and is suitable for batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electromagnetic materials, and specifically relates to a ZIF-67 modified NiFe-LDH absorbing material, a preparation method and an application thereof. Background Art

[0002] LDH, also known as hydrotalcite-like materials, is composed of a positively charged hydroxide layer and negatively charged anions in the interlayer space. These hydrotalcites have the advantages of special structure, large specific surface area, super strong anion exchange capacity, simple synthesis process, low price and environmental friendliness. In recent studies, it was found that NiFe-LDH is a three-dimensional flower-like structure formed by stacking two-dimensional nanosheets. Under the pyrolysis of protective gas Ar, the original flower-like structure has not changed, and the corrosion resistance of the material has been effectively improved. However, its dielectric capacity is relatively weak. At present, there are few studies on NiFe-LDH in the field of electromagnetic wave absorption, which limits its application in this regard. Therefore, there is an urgent need for a material to modify NiFe-LDH to improve its wave absorption characteristics. Summary of the invention

[0003] In view of the deficiencies in the prior art, the object of the present invention is to provide a ZIF-67 modified NiFe-LDH absorbing material, a preparation method and an application thereof, so as to solve the technical problem in the prior art that the electromagnetic wave absorption characteristics of NiFe-LDH materials need to be improved.

[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0005] A ZIF-67 modified NiFe-LDH wave absorbing material, comprising a flower-shaped NiFe-LDH with lamellae, and ZIF-67 polyhedrons embedded between the flower-shaped NiFe-LDH lamellae;

[0006] In the flower-shaped NiFe-LDH, the molar ratio of the Ni source compound to the Fe source compound is (9-1):1;

[0007] The mass ratio of ZIF-67 to NiFe-LDH is 2:(3~5).

[0008] Optionally, the ZIF-67 polyhedron is a hollow regular dodecahedron; the shell of the ZIF-67 polyhedron is a carbon-doped carbon polyhedron, and the core is metallic cobalt.

[0009] Optionally, the diameter of the flower-shaped NiFe-LDH is 7 to 9 um; the diameter of the ZIF-67 polyhedron is 800 to 900 nm.

[0010] The method for preparing any ZIF-67 modified NiFe-LDH absorbing material of the present invention comprises:

[0011] Step 1, ZIF-67 is added to methanol to obtain solution A, NiFe-LDH is added to methanol to obtain solution B, and solution A and solution B are mixed and reacted, then centrifuged, washed, and dried to obtain NiFe-LDH and ZIF-67 precursors;

[0012] Step 2: NiFe-LDH and ZIF-67 precursors are calcined at 500-900° C. for 1-3 h in an argon atmosphere to obtain a ZIF-67 modified NiFe-LDH absorbing material.

[0013] Optionally, the preparation method of NiFe-LDH comprises: mixing Ni salt, Fe salt, urea and NH4F, dissolving in water, and performing hydrothermal reaction at 100-150° C. for 7-10 hours to obtain NiFe-LDH.

[0014] Optionally, the preparation method of ZIF-67 comprises: adding Co salt and dimethylimidazole into methanol, standing at room temperature for 24 hours, washing, centrifuging and drying to obtain ZIF-67.

[0015] Optionally, in step 1, the mass ratio of ZIF-67 to NiFe-LDH is (1-3): (0.3-0.5).

[0016] Optionally, in step 2, the heating rate of calcination is 2 to 5°C / min.

[0017] Application of any ZIF-67 modified NiFe-LDH absorbing material described in the present invention for preparing electromagnetic absorbing material.

[0018] A microwave absorber is obtained by mixing any ZIF-67 modified NiFe-LDH microwave absorbing material described in the present invention with paraffin.

[0019] Compared with the prior art, the present invention has the following technical effects:

[0020] (1) The present invention provides a simple method for preparing ZIF-67 modified NiFe-LDH. There is no method for preparing ZIF-67 modified NiFe-LDH for use as a microwave absorbing material in the prior art.

[0021] (2) The preparation method of the flower-shaped Z@NFL composite material of the present invention has the advantages of simple process, short preparation cycle, low cost, etc., and is suitable for mass production;

[0022] (3) The flower-like Z@NFL composite material of the present invention has an overlapping lamellar structure. By introducing a structural unit composed of a carbon-doped carbon polyhedron as a shell and a metal cobalt as a core, a hollow regular dodecahedron is embedded in LDH lamellar layers with different contents to successfully prepare Z@NFL. The three-dimensional porous structure formed by the two composite materials will produce a large number of heterogeneous interfaces and induce a variety of loss mechanisms and suitable impedance matching characteristics.

[0023] (4) When the Z@NFL composite material of the present invention is used as an electromagnetic wave absorbing material, the loss mechanism is stronger and the impedance matching is better, that is, the electromagnetic wave absorption capability can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0025] Figure 1 Performance spectra of five molar ratios of nickel source and iron source in NiFe-LDH;

[0026] Figure 2 The SEM images of five molar ratios of nickel source and iron source in NiFe-LDH;

[0027] Figure 3 is the XRD pattern of the Z@NFL-4 composite material in Example 1;

[0028] Figure 4 is the Raman spectrum of the Z@NFL-4 composite material in Example 1;

[0029] Figure 5 (ac) is the ZIF-67 precursor in Example 1, (df) is the ZIF-67 derivative, namely Co@NC, and (gi) is the ZIF-67@NiFe-LDH precursor;

[0030] Figure 6 This is the SEM image of the Z@NFL-4 composite material in Example 1;

[0031] Figure 7 This is the XPS spectrum of the Z@NFL-4 composite material in Example 1;

[0032] Figure 8 RL, 3DRL and 3DRL projection spectrum of the Z@NFL-4 composite material in Example 1;

[0033] Fig. 9 RL spectrum of the Z@NFL-5 composite material in Example 2;

[0034] Fig.10 This is the RL spectrum of the Z@NFL-3 composite material in Example 3. DETAILED DESCRIPTION

[0035] The ZIF-67 modified NiFe-LDH absorbing material of the present invention comprises a flower-shaped NiFe-LDH with lamellae, wherein ZIF-67 polyhedrons are embedded between the flower-shaped NiFe-LDH lamellae; in the flower-shaped NiFe-LDH, the molar ratio of the Ni source compound to the Fe source compound is (9-1):1; the mass ratio of ZIF-67 to NiFe-LDH is 2:(3-5). For example, the specific ZIF-67 polyhedron is a hollow regular dodecahedron; the shell of the ZIF-67 polyhedron is a carbon-doped carbon polyhedron, and the core is metal cobalt. More specifically, the diameter of the flower-shaped NiFe-LDH is 7 to 9 um; the diameter of the ZIF-67 polyhedron is 800 to 900 nm. Therefore, the average particle size of the flower-shaped Z@NFL composite material (ZIF-67 modified NiFe-LDH absorbing material) finally prepared is 7 to 9 um; the optimal reflection loss of the Z@NFL composite material to electromagnetic waves at a frequency of 5.43 GHz reaches -77.97 dB; the optimal bandwidth is 6.42 GHz (11.58-18 GHz), and the matching thickness is only 2.02 mm.

[0036] The present invention provides a method for preparing a ZIF-67 modified NiFe-LDH absorbing material. The method uses Ni salt, Fe salt, urea and NH4F as sources and water as a solvent to mix and prepare a mixture A containing Ni source and Fe source, and subjecting the mixture A to a hydrothermal reaction to obtain NiFe-LDH. Then, ZIF-67 is prepared using Co salt (Co(NO3)2) as a Co source, dimethylimidazole as an auxiliary agent, and methanol as a solvent. The prepared flower-shaped NiFe-LDH is added to ZIF-67, and the formed suspension is subjected to a reaction and calcination treatment (calcination at 500-900°C for 1-3h) to finally obtain a flower-shaped Z@NFL composite material. The absorbing material prepared by the method of the present invention has a wide bandwidth, high reflection loss, a simple preparation process, and low cost, and is suitable for mass production. For example, the mass ratio of ZIF-67 to NiFe-LDH in the suspension is 2: (3-5);

[0037] Preferably, the metal compounds used in the present invention are all nitrates, such as the molar ratio of Ni(NO3)2 and Fe(NO3)3 is 7:1, and the amount of water is 80 ml; the reaction temperature of the hydrothermal reaction is 120°C, and the reaction time is 8 h;

[0038] Preferably, the calcination temperature is 600° C., the calcination time is 2 h, and the calcination heating rate is 5° C. / min.

[0039] At the same time, the inventors also studied the influence of different molar ratios of Ni source compounds and Fe source compounds on the properties of the prepared composite material, specifically including: the specific experimental steps of preparing NiFe-LDH by hydrothermal method are: pouring a certain molar ratio of Ni(NO3)2·6H2O and Fe(NO3)3·9H2O, 25mmol urea and 8mmol NH4F into 80ml of deionized water, stirring for 30min to completely dissolve all reagents together, and charging the completely dissolved solution into a 100ml reactor, reacting at 120°C for 8h, washing it with deionized water and anhydrous ethanol several times after the reaction, and finally drying it in a drying oven overnight to obtain a yellow powder, namely NiFe-LDH. Among them, the molar ratios of Ni(NO3)2·6H2O and Fe(NO3)3·9H2O are 9:1, 7:1, 5:1, 3:1, 1:1, respectively, and the total molar number is 4.4mmol. NiFe-LDH was calcined at 600 °C for 2 h under argon protection gas to obtain nickel ferrite. The nickel ferrite sample was homogenized with paraffin in a ratio of 3:7, and the resulting mixture was pressed into a ring with an outer diameter and an inner diameter of about 3.00 mm and 7.00 mm, respectively. The electromagnetic properties were tested in the frequency range of 2 to 18 GHz using a vector network analyzer.

[0040] Figure 1 These are the performance graphs of five proportional samples. A reflection loss below -10dB means 90% of the electromagnetic waves can be absorbed. If the requirements are not met in the graph, it means the sample has no performance. Figure 2 These are SEM images of samples with five ratios. When the molar ratio of nickel to iron is 7:1, the samples have a good morphology.

[0041] Specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical solution of this application fall within the protection scope of the present invention.

[0042] In the following examples, the molar ratio of the Ni source compound to the Fe source compound is 7:1.

[0043] Embodiment 1:

[0044] This example provides a method for preparing a ZIF-67 modified NiFe-LDH absorbing material, which specifically comprises the following steps:

[0045] Step 1, preparing NiFe-LDH precursor;

[0046] Weigh 3.85mmol Ni(NO3)2·6H2O, 0.55mmol Fe(NO3)3·9H2O, 20mmol urea, and 8mmol NH4F, pour into 80ml deionized water, stir for 30min to completely dissolve, put into a 100ml reactor, the temperature of the hydrothermal reaction is 120℃, the reaction time is 8h, and after centrifugal washing and drying, NiFe-LDH precursor is obtained;

[0047] Step 2, preparing ZIF-67 precursor;

[0048] Weigh 0.498 g of Co(NO3)2•6H2O and 0.656 g of dimethylimidazole, pour into 50 ml of methanol, stir until completely dissolved, let stand for 24 h, wash and centrifuge to obtain ZIF-67 precursor;

[0049] Step 3, preparing flower-shaped ZIF-67@NiFe-LDH precursor;

[0050] Weigh 0.4 g of NiFe-LDH and pour it into 25 ml of methanol and stir for 30 min to obtain solution A. Pour 0.2 g of ZIF-67 into 100 ml of methanol and stir for 30 min to obtain solution B. Quickly pour solution A into solution B and stir for 2 h. Wash with anhydrous ethanol and dry to obtain ZIF-67@NiFe-LDH precursor.

[0051] Step 4, preparing flower-shaped Z@NFL composite materials;

[0052] The ZIF-67@NiFe-LDH precursor was calcined at 600°C in a tubular furnace under argon atmosphere, with a reaction heating rate of 5°C / min and a reaction holding time of 2h to obtain a flower-shaped Z@NFL-4 composite material.

[0053] Finally, the product was characterized by XRD, SEM and RAMAN.

[0054] The material sample prepared by the present invention was homogenized with paraffin wax in a ratio of 1:4, and the resulting mixture was pressed into a ring with an outer diameter and an inner diameter of about 3.00 mm and 7.00 mm, respectively, and the electromagnetic properties were tested in a frequency range of 2 to 18 GHz using a vector network analyzer.

[0055] Embodiment 2:

[0056] This example provides a method for preparing a ZIF-67 modified NiFe-LDH absorbing material. The method is basically the same as the preparation method in Example 1, except that in step 3, the mass ratio of ZIF-67 to NiFe-LDH is 2:5. The product is named Z@NFL-5 and is finally characterized by XRD, SEM and RAMAN.

[0057] Embodiment 3:

[0058] This example provides a method for preparing a ZIF-67 modified NiFe-LDH absorbing material. The method is basically the same as the preparation method in Example 1. In step 3, the mass ratio of ZIF-67 to NiFe-LDH is 2:3. The product is named Z@NFL-3 and is finally characterized by XRD, SEM and RAMAN.

[0059] Figure 3 The XRD spectrum of the Z@NFL-4 composite material in Example 1 is shown in the figure. It can be seen from the figure that the test results are completely consistent with the corresponding standard card. The three peaks at 44.5°, 51.8° and 76.2° correspond to the (1 1 1), (2 0 0) and (2 2 0) crystal planes of metal Co (PDF 15-0806), respectively, indicating that Co2+ is reduced to cobalt under the influence of argon and ZIF_67. When 2θ is equal to 44.2°, 51.5° and 75.9°, it corresponds to the (1 1 1), (2 0 0) and (2 2 0) crystal planes of FeNi3 (PDF38-0419)

[54] . In addition, there is an inconspicuous carbon peak at 26°, which corresponds to the (0 0 2) crystal plane of amorphous graphite carbon.

[0060] Figure 4 This is the Raman spectrum of the Z@NFL-4 sample in Example 1 obtained at a laser wavelength of 532 nm. -1 and 1582cm -1 There are two obvious resonance peaks at the position near the D band and the G band (E2g carbon vibration mode). The D band is characteristic of disordered carbon, and the G band is a typical representative of graphite carbon. The ratio of the two peaks (I D / I G ) is usually used to indicate the degree of graphitization. After calculation, it is found that: I of Z@NFL-4 D / I G The value is 0.9832, which shows that the degree of graphitization of the sample is higher after the introduction of ZIF-67, while the defective carbon is smaller, which may improve its conductivity and enhance the related loss capacity.

[0061] Figure 5 (ac) are the ZIF-67 precursors in Example 1. It can be seen that ZIF-67 is a regular dodecahedron structure, each surface is very smooth, and the sizes are slightly different. The size of each particle is between 800-900nm. Figure 5 (df) is a ZIF-67 derivative, namely Co@NC. Under high-temperature calcination, the sample contour shrinks and the edges and corners become more obvious, but the overall morphology of the regular dodecahedron is still retained. Figure 5 (gi) is the ZIF-67@NiFe-LDH precursor, in which the dodecahedral particles are evenly embedded in the three-dimensional nanoflowers.

[0062] Figure 6 This is the SEM image of the Z@NFL-4 composite material in Example 1. After annealing at high temperature, the sample still maintains the original flower-like structure with an average flower diameter of about 8um, but the thickness and roughness of the nanosheets are significantly increased. ZIF-67 and NiFe-LDH are successfully hybridized, and Co@NC particles are uniformly inserted into the nanosheet layer of the flower-like LDH.

[0063] Figure 7 This is the XPS spectrum of the Z@NFL-4 composite material in Example 1. The full-width scan spectrum in the figure shows the presence of six elements: C, N, O, Co, Ni and Fe. Figure 7 (a) shows the three peaks separated from the C 1S spectrum, namely CC / C=C (284.8 eV), CN (285.6 eV) and OC=O (289.3 eV). Figure 7 (b) shows the N 1S spectrum, which has three characteristic peaks. Figure 7 (c)), O1, O2 and O3 define three peaks at 529.8eV, 531.2eV and 532.5eV respectively. The Co2p spectrum has seven peaks ( Figure 7 (d)). Figure 7 (e) shows the Ni 2p spectrum. Figure 7 (f) shows the Fe 2P spectrum.

[0064] Figure 8 The RL, 3DRL and 3DRL projection spectra of the Z@NFL-4 composite material in Example 1. It can be seen from the figure that the optimal bandwidth is 6.42GHz, ranging from 11.58 to 18GHz, and the matching thickness is only 2.02mm. In addition, when the frequency and thickness are .03GHz and 4.43mm respectively, the minimum reflection loss is -50.50dB.

[0065] like Fig. 9 The minimum reflection loss of Z@NFL-5 at 5.43 GHz is as high as -77.97 dB, and the corresponding effective absorption bandwidth is 5.25 GHz (12.75-18 GHz) when the thickness is 1.82 mm.

[0066] like Fig.10 This is the RL diagram of Z@NFL-3. The minimum reflection loss is -13.03dB at 16.65GHz, and the effective absorption bandwidth is 4.53GHz (13.47-18GHz) at 1.58mm.

[0067] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0068] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0069] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A ZIF-67 modified NiFe-LDH absorbing material, characterized in that: It includes a flower-shaped NiFe-LDH with flakes, and ZIF-67 derivative Co@NC is embedded between the flower-shaped NiFe-LDH flakes; The ZIF-67 derivative Co@NC is a hollow regular dodecahedron; the shell of the ZIF-67 derivative Co@NC is a nitrogen-doped carbon polyhedron, and the core is metallic cobalt; The diameter of the flower-shaped NiFe-LDH is 7-9um; the diameter of the ZIF-67 derivative Co@NC is 800-900nm; The preparation method of the ZIF-67 modified NiFe-LDH wave absorbing material comprises: Step 1, ZIF-67 is added to methanol to obtain solution A, NiFe-LDH is added to methanol to obtain solution B, and solution A and solution B are mixed and reacted, and then centrifuged, washed, and dried to obtain NiFe-LDH and ZIF-67 precursors; the mass ratio of ZIF-67 to NiFe-LDH is 2: (3-4); Step 2: NiFe-LDH and ZIF-67 precursors are calcined at 500-900° C. for 1-3 h in an argon atmosphere to obtain a ZIF-67 modified NiFe-LDH absorbing material; The preparation method of NiFe-LDH comprises: mixing Ni salt, Fe salt, urea and NH4F and dissolving them in water, and hydrothermally reacting them at 100-150° C. for 7-10 hours to obtain NiFe-LDH; the molar ratio of Ni salt to Fe salt is 7:

1.

2. The method for preparing the ZIF-67 modified NiFe-LDH absorbing material according to claim 1, characterized in that: include: Step 1, ZIF-67 is added to methanol to obtain solution A, NiFe-LDH is added to methanol to obtain solution B, and solution A and solution B are mixed and reacted, then centrifuged, washed, and dried to obtain NiFe-LDH and ZIF-67 precursors; Step 2: NiFe-LDH and ZIF-67 precursors are calcined at 500-900° C. for 1-3 h in an argon atmosphere to obtain a ZIF-67 modified NiFe-LDH absorbing material; The preparation method of the NiFe-LDH comprises: Ni salt, Fe salt, urea and NH4F are mixed and dissolved in water, and hydrothermally reacted at 100-150°C for 7-10h to obtain NiFe-LDH.

3. The method for preparing the ZIF-67 modified NiFe-LDH absorbing material according to claim 2, characterized in that: The preparation method of ZIF-67 comprises: Co salt and dimethylimidazole were added to methanol, allowed to stand at room temperature for 24 h, and then washed, centrifuged and dried to obtain ZIF-67.

4. The method for preparing the ZIF-67 modified NiFe-LDH absorbing material according to claim 2 or 3, characterized in that: In the step 2, the heating rate of calcination is 2-5°C / min.

5. Use of the ZIF-67 modified NiFe-LDH absorbing material according to claim 1 for preparing electromagnetic absorbing materials.

6. A microwave absorbent, characterized in that: The ZIF-67 modified NiFe-LDH absorbing material according to claim 1 is mixed with paraffin.

Citation Information

Patent Citations

  • Magnetic metal and carbon composite wave-absorbing material derived from layered double magnetic metal hydroxides and preparation method of magnetic metal and carbon composite wave-absorbing material

    CN114845538A